"There's Nothing Wrong With You": Pain-Related Stigma in Adolescents With Chronic Pain. (6th December 2021) - Wakefield, Emily O; Belamkar, Vaishali; Litt, Mark D; Puhl, Rebecca M; Zempsky, William T
Abstract: Objective: Adolescents with chronic pain often experience symptom disbelief and social rejection by others secondary to "medically unexplained" symptoms. Although chronic pain is common in adolescents, limited research has conceptualized these social experiences as pain-related stigma in this population. The purpose of this study was to identify and describe pain-related stigma among adolescents with chronic pain and their parents using focus group methodology. Methods: Five adolescent focus groups ( N = 18; Age M = 15.33 years, SD = 1.28) and three parent focus groups ( N = 9) were conducted. Directed content analysis was used to analyze focus group transcripts. Stigma categories were developed a priori (Felt Stigma, Anticipated Stigma, Internalized Stigma, Concealment, and Controllability) and new categories emerged during analysis. Two coders reached 87.16% agreement for all groups (adolescent group: 90.34%; Parent group: 79.55%) and consensus was achieved for discordant codes. Results: Adolescents and their parents endorsed pain-related stigma across all social domains. Analyses revealed four main categories for both groups (a) Felt Stigma (subcategories: pain dismissal, faking or exaggerating, and mental health stigma), (b) Anticipated Stigma and Concealment, (c) Internalized Stigma, and (d) Sources of Pain-Related Stigma (subcategories: pain invisibility, lack of chronic pain knowledge, lack of understanding, and controllability). Conclusions: Adolescents with chronic pain experience pain-related stigma from medical providers, school personnel, family members, and peers, which may have negative social and health implications. More research is needed to evaluate the link between pain-related stigma and health outcomes for adolescents with chronic pain. Clinical approaches targeting pain-related stigma are discussed.